2006
DOI: 10.1100/tsw.2006.108
|View full text |Cite
|
Sign up to set email alerts
|

ECG Changes in 8-Year-Old Boy with Pulmonary Edema after Head Injury

Abstract: This is a case story of an 8-year-old boy with no prior history of cardiac disease who developed acute pulmonary edema with ECG changes similar to transmural myocardial infarction after basilar skull fracture. Biochemical evaluation showed elevated total creatine kinase activity –1,350 U/L with 12% MB isoenzyme fraction. The brain scan on admission showed cerebral edema with ethmoidal sinuses hemorrhage. Neurogenic pulmonary edema following CNS damage is an extremely rare entity in the pediatric population and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Patients who survive the initial insult usually have a rapid cardiopulmonary recovery without late onset morbidity [5,6]. NPE and NSM are rare in children but have been reported with trauma [7][8][9][10][11], hemorrhage [12][13][14][15][16], seizure [17], tumor-related obstructive hydrocephalus [4,18], viral encephalitis [19][20][21][22], ketamine toxicity [23], and following decompression of Chiari malformations [24]. Johnson et al [4] reported two cases of NSM and pulmonary edema secondary to acute hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who survive the initial insult usually have a rapid cardiopulmonary recovery without late onset morbidity [5,6]. NPE and NSM are rare in children but have been reported with trauma [7][8][9][10][11], hemorrhage [12][13][14][15][16], seizure [17], tumor-related obstructive hydrocephalus [4,18], viral encephalitis [19][20][21][22], ketamine toxicity [23], and following decompression of Chiari malformations [24]. Johnson et al [4] reported two cases of NSM and pulmonary edema secondary to acute hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%